The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s41241-017-0011-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genomics and epidemiology for gastric adenocarcinomas

Abstract: Whereas the pathological aspects of Gastric Adenocarcinomas (GACs) have been well defined, the actual knowledge of its genesis and evolution remains to be translated to better diagnosis and to more effective therapeutics. As a consequence, the current treatment modalities are not yet able to modify the natural history of the disease, which still presents high mortality-rates worldwide. In this review we highlight the current status of relevant epidemiologic, therapeutic and genomics aspects of GACs and point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 100 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…A report revealed that the region with the highest incidence of gastric cancer is East Asia, particularly China, with an annual incidence of approximately 4–6 cases per 10,000 individuals (3). In addition, the National Cancer Institute data indicated that the incidence and diagnosis of this disease is mainly between the ages of 60–70 years, and the majority of patients have a poor prognosis due to diagnosis in the late stages of the disease (4). Approximately 90% of stomach tumors are adenocarcinomas, which are classified into two main histologic types: High differentiated or intestinal-type gastric cancer; and undifferentiated or diffuse-type gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A report revealed that the region with the highest incidence of gastric cancer is East Asia, particularly China, with an annual incidence of approximately 4–6 cases per 10,000 individuals (3). In addition, the National Cancer Institute data indicated that the incidence and diagnosis of this disease is mainly between the ages of 60–70 years, and the majority of patients have a poor prognosis due to diagnosis in the late stages of the disease (4). Approximately 90% of stomach tumors are adenocarcinomas, which are classified into two main histologic types: High differentiated or intestinal-type gastric cancer; and undifferentiated or diffuse-type gastric cancer.…”
Section: Introductionmentioning
confidence: 99%